Performance of Hybrid Rice varieties JRH-5 and JRH-19in front line demonstrations under irrigated conditions in agro climatic zone Chhattisgarh plains of Madhya Pradesh - Bisen, Uttam Kumar; Gaur, Vikram Singh; Solanki, Ramkrishna Singh (International Journal of Scientific Research in Biological Sciences, 2024)
Frontline demonstrations were conducted with scientific package and practices in the farmer’s fieldslocated in the Chhattisgarh plain agro climatic zone of Balaghat district, Madhya Pradesh to evaluate the performance oftwo short duration hybrid rice varieties JRH-5 and JRH-19 under irrigated ecosystem during the Kharif season of two consecutive years2016 and 2017. The data on yield and economics of demonstrated plotswhen comparedwith the farmers rice cultivating practices on the popular rice variety MTU-1010 revealed thatboth the Hybrid Rice varieties performed superior to MTU1010. JRH-5 and JRH-19 with improved production technologies showed increasedmean grain yield by 27.64% over existing farmers practices with only Rs. 2638/ha extra expenditureon inputs. In addition to this, the mean extension gap (11.88 q/ha) and mean IBCR (5.80)recorded weresufficiently high to motivatefarmers to adoptJRH-5 and JRH-19 with the improved rice production technology.